INNO IT Framework, Innovation in IT Governance - Šimková, Eva; Basl, Josef, 1961-; Molnár, Zdeněk, 1939-; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2008)
The main topic of this thesis is IT innovation management which is very up to date theme as a research within the thesis documents. IT innovation should be managed jointly with the IT Governance to support effectiveness of IT and competitiveness of the whole company.
Vedoucí práce: Josef Basl
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Způsob přístupu: Internet
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2009
Rok obhajoby 2009
Keywords: informatika [obor disert. práce]; disertace; dissertations